The Issue of (Standard Arabic and Colloquial Arabic) in Mass and Interactive Media: Characteristics and Perspectives - salami, saidan (El Omda in Linguistics and Discourse Analysis, 2018)
The issue of the duality between Standard Arabic (fuṣḥā) and Colloquial Arabic (ʿāmmiyya) in mass media must be considered in light of the immense power and influence that media holds today—especially in the era of the second communication revolution (the emergence of electronic media such as radio and television) and the third (the Internet)—and its impact on people in our time. In reality, this prominent position of media carries within it opportunities for a positive influence that can serve human development, elevate expression, and enhance linguistic eloquence, if media tools are used effectively to present meaningful and beneficial content. At the same time, it also entails risks of a negative influence if dominant forces exploit media to erode identity, promote linguistic corruption, and spread superficial or degrading values. Our contribution to this discussion lies in presenting reflections shaped by personal observation and ongoing dialogues on the subject.